New Type of Roundabout: Dual One-Lane Roundabouts on Two Levels with Right-Hand Turning Bypasses – ’’Target Roundabout’’ - Tollazzi, Tomaž; Jovanović, Goran; Renčelj, Marko (Promet - Traffic&Transportation, 2013)
The problems of low level traffic safety on multi-lane roundabouts have been resolved in various ways in different countries, usually by using alternative types of roundabouts that reduce the number of conflict points. Alternative types of roundabouts typically differ from ’normal’ or ’standard’ roundabouts in one or more design elements, as their implementation purposes could also be specific. Today, several different types of roundabouts are already in use (’mini’, ’double mini’, ’dumb-bell’, those ’with joint splitter islands’ (’dog-bone’), those ’with a spiralling circular carriageway’ (’turbo’), those ’with depressed lanes for right-hand turners’ (’flower’) etc.). This paper introduces a new type of roundabout, dual one-lane roundabouts on two levels with right-hand turning bypasses, namely the ’target roundabout’. This paper describes and analyses their design, traffic safety, and capacity characteristics, compared with the standard two–lane roundabouts.